Fabrication of MnO2 Nanocomposite on GO Functionalized with Advanced Electrode Material for Supercapacitors. (21st January 2022) - Kumar, R. Ranjith; Thanigaivel, S.; Priya, A. K.; Karthick, Alagar; Malla, Chandrabhanu; Jayaraman, P.; Muhibbullah, M.; Alshgari, Razan A.; Karami, Abdulnasser Mahmoud
Abstract : A new strategy for supercapacitor formation was carried out in the study using electrodes made of graphene oxide (GO) and manganese dioxide (MnO2 ) nanocomposites. To the present knowledge, only a few investigations have been carried out concerning the synthesis of GO-MnO2 -based nanocomposites and their electrochemical properties, with varying mass ratios, as well as the change in electrochemical properties of their components as MnO2 and GO were tested individually for the enhanced stability and performances. A synthetic method was performed successfully to manufacture MnO2 /GO nanocomposites. The findings of the present study show that the composites have a lot of potential as an effective conduction property. A composite of graphene oxide supported manganese dioxide nanocomposites fabricated with the simple soft chemical route. As-prepared nanocomposites can be improved in performance by the interactions between GO and MnO2 .